2022
DOI: 10.1002/pc.26938
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue, fracture toughness and DMA of biosilica toughened epoxy with stacked okra fiber and Al 2024‐T3 fiber metal laminate composite

Abstract: In this present study, a natural fiber-based fiber metal laminate (FML) was fabricated for various engineering applications. The primary aim of this present investigation was to study the effect of adding natural fiber along with metal and the effect of the surface-treatment process on the reinforcements on load-bearing and thermo-mechanical properties. Okra fiber woven mat, aluminum 2024-T3 foil and rice husk-derived biosilica were used as reinforcements.For surface treatment, the metal foil was sandblasted w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…[ 23 ] This is due to the fact that the rate of microcracks creation and transmission accelerates with increasing stress applied, causing the composites to deform plastically. [ 24 ] For composite designations N11 and N21, additional inclusions of maize husk fiber amounting to 30 vol% enhanced the fatigue life cycles by 97.01% and 97.39%, respectively. The dispersed reinforcements are distributed uniformly throughout the composite as a result of this increase in values caused by the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…[ 23 ] This is due to the fact that the rate of microcracks creation and transmission accelerates with increasing stress applied, causing the composites to deform plastically. [ 24 ] For composite designations N11 and N21, additional inclusions of maize husk fiber amounting to 30 vol% enhanced the fatigue life cycles by 97.01% and 97.39%, respectively. The dispersed reinforcements are distributed uniformly throughout the composite as a result of this increase in values caused by the matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent to this, a number of investigations have been conducted on the utilization of okra fiber‐reinforced composites, which have exhibited considerable potential. Noteworthy examples include the effect of fiber content% of okra/PVA composites as reported by Khan et al, 34 the tensile characterization of okra/polyester composites as demonstrated by Srinivasababu et al, 35 the exploration of thermo‐mechanical and morphological properties of okra/starch composites as conducted by Guleria et al, 36 the investigation of okra/urea formaldehyde composites as presented by Khan et al, 37 the examination of okra/tamarind kernel/epoxy composites as reported by Sivakumar et al, 38 while Ramesh et al 39 studied the fatigue and dynamic mechanical properties of okra/aluminum 2024‐T3 foil/epoxy composites. Recent studies have focused on various aspects of okra fiber, including its extraction and surface modification using environmentally friendly methods reported by Kocak et al, 40 among the other investigations Khan et al 41 have explored the effects of chemical treatments and degumming methods on the fiber, Khan et al 42 also analyzed the impact of alkalization on biologically degummed fiber.…”
Section: Introductionmentioning
confidence: 99%
“…5 The process takes a relatively long time to complete the thermoset curing and ensure the high-performance of aircraft components. 5,10 However, when FMLs are used in mass production and applied in the civil field, efficiency and low cost must be considered. Continuous fiber-reinforced thermoplastic (FRTP) composites display excellent fracture toughness in contrast with fiber-reinforced thermoset counterparts.…”
Section: Introductionmentioning
confidence: 99%